Cosmetic Surgery and Body Image in Adolescents: A Psycho-Sociological Analysis of the Causes and Effects - Souad, Merah; Ramdane, Tahraoui; Ghada, Tahraoui; Khan, Mariya Seemin (2018)
This conceptual paper examines the impact of body image on Adolescents’ quest for cosmetic surgery. A reflective analysis of the literature was utilized. Factors shaping one’s perception of own body was explained .The causes and effects were also highlighted. The study has shown, that there has been a definite increase in the number of teenagers undergoing various cosmetic procedures and that a correlation can be drawn between this quest and poor body image, which could have alarming physical, social and emotional consequences. As for the causes the study has concluded that the quest to achieve a better appearance is mainly due to the socially portrayed “ideal beauty standards”. There is a consensus among researchers and medical practitioners that, the main pushing factor towards going under the knife is social especially enhancement procedures. It was also found that; the media and the rigorous capitalist’s campaign to boost consumerism is behind the rampant body idealization culture. In addition, the study has also shown that the availability of advanced cosmetic procedures in some countries has led to the increase of adolescents’ seeking body modifications.